PENGARUH ALELOPATI EKSTRAK RIMPANG ALANG-ALANG (Imperata cylindrica) SEBAGAI BIOHERBISIDA BAGI GULMA ALANG-ALANG - Lismaini Lismaini (STIPER Dharma Wacana Metro, 2021)
Reeds grass (Imperata cylindrica (L.) Beauv.) is a weed plant growing rapidly disturb agriculture and plantation crops. The aim of the study was to determine the effect of giving reed grass rhizome extract in various concentrations and how to apply it as well as the interaction of both on reed grass weeds. The research design used was a complete randomized block design with two factors, namely the formulation reed grass rhizome extract (levels 20%, 30%, 40%, 50% and control) and how the application (via the roots and crown), each of which is repeated as many as 10 replications. Data were analyzed statistically using ANOVA table and to examine the two middle values used Test Least Significant Difference (LSD) at 5% level. The hypothesis is suspected substance residues of reed grass rhizome extract is effective in inhibiting the vegetative growth of reeds grass. The results showed that (1) Levels of substance extract residues reed grass rhizome of 20% - 50% significantly reduced the growth of reeds grass which marked the low canopy observation length, root length, shoot dry weight and root dry weight, (2) Application through real root suppress the growth of reeds which marked the low canopy observation length, shoot dry weight and root dry weight, and the percentage of deaths.